Comparison between hydrogen-rich biogas production from conventional pyrolysis and microwave pyrolysis of sewage sludge: is microwave pyrolysis always better in the whole temperature range?. (1st July 2021) - Liu, Yanting; Chen, Tan; Gao, Bingli; Meng, Ruihong; Zhou, Ping; Chen, Ganyu; Zhan, Yuyu; Lu, Wenjing; Wang, Hongtao
Abstract: To investigate the influence of the pyrolysis temperature on biogas production from sewage sludge, conventional pyrolysis and microwave pyrolysis were carried out in the temperature range from 600 °C to 900 °C and all products were analyzed. With the temperature increasing, the product yields for conventional pyrolysis varied significantly, while those for microwave pyrolysis changed quite slightly. In conventional pyrolysis, the yield of H2 increased from 1.26 mmol/g at 600 °C to 9.07 mmol/g at 900 °C, while it was varied only from 1.84 mmol/g to 3.67 mmol/g in microwave pyrolysis. Under microwave pyrolysis, a high ratio of H/C indicated that more hydrogen atoms converted directly to tar instead of being released into biogas, which was caused by side reactions (such as the hydrogen transfer reaction). More aromatic compounds in the tar during microwave pyrolysis illustrated that the hydrogen transfer reaction was enhanced by microwave at the higher temperatures. It has been found that the sludge microwave pyrolysis had some drawbacks for the hydrogen-rich biogas production, because it could promote some side reactions to suppress the H2 production, especially the hydrogen transfer reaction. Highlights: From 600 °C to 900 °C, the yields of hydrogen changes in different trends. Microwave promotes hydrogen transfer reaction to suppress H2 yield from pyrolysis. Saturation of tar obtained from microwave pyrolysis is higher due to side reactions. More aromatic compounds are found in the tar generated from microwave pyrolysis. A possible reaction mechanism under microwave pyrolysis is described.